Nursing Intervention With Combined Psychoreligious Therapy In Patients With Auditory And Visual Hallucinations A Case Report - Setiani, Haniifah Setiani; Hidayati, Nur Oktavia; Hernawaty, Taty (JURNAL CITRA KEPERAWATAN, 2025)
Hallucinations are a common symptom often experienced by people with schizophrenia. Treatment can be carried out through psychiatric nursing care combined with psychoreligious therapy. This study aims to describe the application of a combination of nursing care and psychoreligious therapy in patients diagnosed with sensory perception disorders: auditory and visual hallucinations. The method used was a clinical case report with five stages of the nursing process, from assessment to evaluation. The intervention was conducted over seven days, and psychoreligious therapy was administered twice daily for 10–20 minutes per session. The study subject was a patient, Mr. I, diagnosed with schizophrenia and experiencing auditory and visual hallucinations. The patient had a history of repeated hospitalizations at the psychiatric hospital with the same symptoms since 2019. Mr. I presented with complaints of laughing and talking to himself. The patient’s speech was incoherent, his affect was labile, he had difficulty focusing, and he exhibited a flight of ideas. The results showed that this intervention was effective for Mr. I, as the patient was able to recognize, dismiss, and redirect hallucinations independently, showed improved adherence to treatment, was able to maintain focus during conversations, was calmer, could open up emotionally, and experienced a reduction in the frequency of hallucinations. The conclusion of this study is that the combination of nursing care and psychoreligious therapy can be proven effective in enhancing the ability of schizophrenia patients to manage auditory and visual hallucinations independently.